Carbon nitride-based composite material for photocatalytic degradation and preparation method thereof
By introducing sodium bicarbonate and cadmium sulfide into carbon nitride materials and modifying with thiol cyclodextrin, the problem of insufficient performance of carbon nitride photocatalytic materials is solved, and the effect of efficient degradation of dye wastewater is achieved.
Patent Information
- Application Number
- CN202411056690.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-02
- Publication Date
- 2024-12-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing carbon nitride photocatalytic properties of the photocatalytic properties of existing carbon nitride photocatalytic materials are weak and have insufficient stability, making it difficult to effectively degrade pollutants in dye wastewater.
Carbon nitride is prepared by adding sodium bicarbonate as an auxiliary agent to the carbon nitride precursor, and cadmium sulfide is generated on the carbon nitride, and then thiol cyclodextrin is introduced to form a carbon nitride material with structural defects, enhancing photocatalysis and accelerate the transfer and separation of photogenerated electrons and holes through the synergistic action of cadmium sulfide and carbon nitride, and improve stability by modifying thiol cyclodextrin.
The photocatalytic degradation ability and stability of carbon nitride composite materials is significantly improved, the conversion efficiency of light energy is enhanced, the agglomeration of cadmium sulfide is reduced, and the solubility and stability in water are improved.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photocatalytic materials, in particular to a carbon nitride-based composite material for photocatalytic degradation and a preparation method thereof. Background Art
[0002] Water pollution has become an increasingly serious problem that endangers human health and the natural environment. Wastewater not only destroys the beauty of water bodies and affects people's visual experience, but also reduces the intake of sunlight, hinders the photosynthesis of aquatic plants, and causes toxic effects on aquatic organisms such as fish and algae. It can even form aromatic amine carcinogenic compounds in an anaerobic environment, causing serious harm to human health. At present, dye wastewater has become one of the most difficult pollutants to treat due to its high COD, large chromaticity, complex components, high organic matter and salt content, high acidity (alkalinity), rapid changes in water quality and quantity, and a large amount of teratogenic and carcinogenic substances. If these wastewaters are discharged directly, they will cause pollution in my country's soil, water sources, etc., and seriously affect the ecological environment. Therefore, how to degrade pollutants in dye wastewater, reduce the toxicity of wastewater, and improve the biodegradability of wastewater has attracted widespread attention.
[0003] Carbon nitride photocatalytic materials are commonly used to degrade pollutants in dye wastewater, but nitrogen still has many problems. Carbon nitride composite materials have weak photocatalytic performance and insufficient stability. Therefore, this application studies and prepares a carbon nitride composite material for photocatalytic degradation to solve this problem. Summary of the invention
[0004] The object of the present invention is to provide a carbon nitride-based composite material for photocatalytic degradation and a preparation method thereof, so as to solve the problems raised in the above background technology.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a preparation method for carbon nitride-based composite materials for photocatalytic degradation, the preparation method for carbon nitride-based composite materials for photocatalytic degradation is: preparation of carbon nitride; preparation of carbon nitride-cadmium sulfide; preparation of carbon nitride-based composite materials for photocatalytic degradation.
[0006] Preferably, a carbon nitride-based composite material for photocatalytic degradation and a preparation method thereof comprises the following specific steps:
[0007] (1) Melamine, urea and sodium bicarbonate are mixed and fully ground, and then passed through a 200-mesh sieve to obtain a melamine mixture. The mixture is transferred to a muffle furnace, heated to 520° C. at a rate of 2 to 4° C. / min, kept warm for 3 to 4 hours, cooled naturally to room temperature, ground again, and dispersed in 2% dilute nitric acid having a mass fraction of 10 times that of the melamine mixture, stirred at room temperature and 800 to 1200 rpm for 6 to 8 hours, filtered to obtain a solid, washed with ultrapure water until the washing liquid is neutral, and finally dried in a 120° C. oven for 12 hours to obtain carbon nitride;
[0008] (2) placing dodecylamine in a polytetrafluoroethylene-lined autoclave, heating in a water bath at 50° C. and stirring at 800-1200 rpm for 10-20 min, adding cadmium acetate in an amount of 0.15-0.2 times the mass of dodecylamine, continuing to stir until completely dissolved, continuing to add thioacetamide in an amount of 0.18-0.22 times the mass of dodecylamine and carbon nitride in an amount of 0.4-0.5 times the mass of dodecylamine, transferring the autoclave to an oven, adjusting the temperature to 150-180° C., keeping the temperature for 12-15 h, cooling to room temperature, centrifuging to obtain a carbon nitride-cadmium sulfide wet material, washing the carbon nitride-cadmium sulfide wet material, placing the carbon nitride-cadmium sulfide wet material in a drying oven at 60-80° C., and drying for 12 h to obtain carbon nitride-cadmium sulfide;
[0009] (3) Dispersing carbon nitride-cadmium sulfide in a thiol cyclodextrin solution with a mass of 10 to 15 times that of carbon nitride-cadmium sulfide, stirring in the dark at room temperature and 1200 to 1500 rpm for 48 hours, adding acetone with a mass of 5 to 8 times that of carbon nitride-cadmium sulfide, centrifuging at 7000 rpm for 3 to 5 minutes to obtain a carbon nitride material, washing the carbon nitride material with acetone for 3 to 5 times, and drying it in a drying oven at 60 to 80°C for 3 to 5 hours to obtain a carbon nitride-based composite material for photocatalytic degradation.
[0010] Preferably, in the above step (1), the mass ratio of melamine, urea and sodium bicarbonate is 4:2:1 to 5:2.5:1.
[0011] Preferably, in the above step (2): during washing, the carbon nitride-cadmium sulfide wet material is washed alternately with ethanol and ultrapure water for 6 to 8 times.
[0012] Preferably, in the above step (3): the method for preparing the mercaptocyclodextrin solution is: dispersing β-mercaptocyclodextrin in ultrapure water with a mass of 2 to 3 times that of β-mercaptocyclodextrin, ultrasonically dispersing at 20 to 30 kHz for 1 to 2 minutes, adding methanol with a mass of 0.03 to 0.05 times that of β-mercaptocyclodextrin and chloroform with a mass of 0.03 to 0.05 times that of β-mercaptocyclodextrin, and finally adjusting the pH to 11 with tetramethylammonium hydroxide to obtain a mercaptocyclodextrin solution.
[0013] Preferably, the carbon nitride-based composite material for photocatalytic degradation obtained by the preparation method of the carbon nitride-based composite material for photocatalytic degradation includes the following raw materials in weight fractions: 5 to 10 parts of carbon nitride-cadmium sulfide and 50 to 150 parts of mercaptocyclodextrin solution; the carbon nitride-cadmium sulfide is prepared by first preparing carbon nitride with melamine, urea and sodium bicarbonate, and then generating cadmium sulfide on the carbon nitride.
[0014] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0015] When preparing the carbon nitride composite material for photocatalytic degradation, the present invention first adds a small amount of sodium bicarbonate as an auxiliary agent to the carbon nitride precursor to prepare carbon nitride, then generates cadmium sulfide on the carbon nitride, and finally introduces mercaptocyclodextrin;
[0016] A small amount of sodium bicarbonate is added as an auxiliary agent during the thermal polymerization of precursors melamine and urea, and then doping and impurities are removed to obtain carbon nitride with internal structural defects; during the high-temperature polymerization process, sodium bicarbonate and melamine react to generate sodium cyanate and form sodium doping, and ammonia and carbon dioxide generated by the decomposition of urea are used to form pores. After removing impurities and doping, structural defects located in the conjugated layer are formed in the carbon nitride, and the pores formed by the combination of defects form pathways. These pathways do not change the band structure of carbon nitride, so that the surface area of carbon nitride is increased, thereby enhancing the photocatalytic ability;
[0017] Cadmium sulfide is modified on carbon nitride with a two-dimensional planar layered stacking structure. The synergistic effect of cadmium sulfide and carbon nitride accelerates the rapid transfer and separation of photogenerated electrons and holes, making cadmium sulfide and carbon nitride photocatalysts for each other, thereby improving the conversion efficiency of light energy. By utilizing the coordination effect between thiol and cadmium element, thiol cyclodextrin is modified on cadmium sulfide. In aqueous solution, cyclodextrin is used as a surface ligand to enhance the solubility and stability of cadmium sulfide in water, reduce the aggregation of cadmium sulfide, reduce the aggregation of carbon nitride composite materials, and improve the stability of carbon nitride composite materials. DETAILED DESCRIPTION
[0018] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0019] Photocatalytic activity: The same mass of the carbon nitride-based composite material prepared in the example and the comparative example for photocatalytic degradation was irradiated with the same mass of 4 mg / L methylene blue solution under visible light of a xenon lamp for 8 h for degradation, and the remaining methylene blue concentration in the methylene blue solution was tested by a spectrophotometer.
[0020] And calculate the degradation rate;
[0021] Photocatalytic stability: The carbon nitride-based composite material used for photocatalytic degradation after being degraded by methylene blue solution was dried, and then subjected to a secondary photocatalytic activity test.
[0022] Example 1
[0023] A carbon nitride composite material for photocatalytic degradation, mainly comprising, by weight:
[0024] 5 parts of carbon nitride-cadmium sulfide, 50 parts of mercaptocyclodextrin solution
[0025] A preparation method for photocatalytic degradation of carbon nitride-based composite materials, the preparation method for photocatalytic degradation of carbon nitride-based composite materials is:
[0026] (1) Melamine, urea and sodium bicarbonate are mixed in a mass ratio of 4:2:1 and fully ground. After grinding, the mixture is passed through a 200-mesh sieve to obtain a melamine mixture. The mixture is transferred to a muffle furnace, heated to 520°C at 2°C / min, kept warm for 3 hours, cooled naturally to room temperature, ground again, and dispersed in 2% dilute nitric acid with a mass fraction of 10 times the mass of the melamine mixture. The mixture is stirred at room temperature and 800 rpm for 6 hours, filtered to obtain a solid, washed with ultrapure water until the washing liquid is neutral, and finally dried in a 120°C ancient wind drying oven for 12 hours to obtain carbon nitride;
[0027] (2) placing dodecylamine in a polytetrafluoroethylene-lined autoclave, heating in a water bath at 50° C. and stirring at 800 rpm for 10 min, adding cadmium acetate in an amount of 0.15 times the mass of dodecylamine, continuing to stir until completely dissolved, continuing to add thioacetamide in an amount of 0.18 times the mass of dodecylamine and carbon nitride in an amount of 0.4 times the mass of dodecylamine, transferring the autoclave to an oven, adjusting the temperature to 150° C., keeping the temperature for 12 h, cooling to room temperature, centrifuging to obtain a carbon nitride-cadmium sulfide wet material, washing the carbon nitride-cadmium sulfide wet material with ethanol and ultrapure water alternately for 6 times, placing it in a drying oven at 60° C., and drying it for 12 h to obtain carbon nitride-cadmium sulfide;
[0028] (3) β-mercaptocyclodextrin was dispersed in ultrapure water with a mass of 2 times that of β-mercaptocyclodextrin, ultrasonically dispersed at 20 kHz for 1 min, methanol with a mass of 0.03 times that of β-mercaptocyclodextrin and chloroform with a mass of 0.03 times that of β-mercaptocyclodextrin were added, and finally the pH was adjusted to 11 with tetramethylammonium hydroxide to obtain a thiolcyclodextrin solution; carbon nitride-cadmium sulfide was dispersed in a thiolcyclodextrin solution with a mass of 10 times that of carbon nitride-cadmium sulfide, stirred at room temperature and 1200 rpm in a dark environment for 48 h, acetone with a mass of 5 times that of carbon nitride-cadmium sulfide was added, and centrifuged at 7000 rpm for 3 min to obtain a carbon nitride material, and the carbon nitride material was washed with acetone 3 times and dried in a drying oven at 60°C for 3 h to obtain a carbon nitride-based composite material for photocatalytic degradation.
[0029] Example 2
[0030] A carbon nitride composite material for photocatalytic degradation, mainly comprising, by weight:
[0031] 10 parts of carbon nitride-cadmium sulfide, 150 parts of mercaptocyclodextrin solution
[0032] A preparation method for photocatalytic degradation of carbon nitride-based composite materials, the preparation method for photocatalytic degradation of carbon nitride-based composite materials is:
[0033] (1) Melamine, urea and sodium bicarbonate are mixed in a mass ratio of 5:2.5:1 and fully ground. After grinding, the mixture is sieved through a 200-mesh sieve to obtain a melamine mixture. The mixture is transferred to a muffle furnace, heated to 520°C at a rate of 4°C / min, kept warm for 4 hours, cooled naturally to room temperature, ground again, and dispersed in 2% dilute nitric acid with a mass fraction of 10 times the mass of the melamine mixture. The mixture is stirred at room temperature and 1200 rpm for 8 hours, filtered to obtain a solid, washed with ultrapure water until the washing liquid is neutral, and finally dried in a 120°C ancient wind drying oven for 12 hours to obtain carbon nitride;
[0034] (2) placing dodecylamine in a polytetrafluoroethylene-lined autoclave, heating in a water bath at 50° C. and stirring at 1200 rpm for 20 min, adding cadmium acetate in an amount of 0.2 times the mass of dodecylamine, continuing to stir until completely dissolved, continuing to add thioacetamide in an amount of 0.22 times the mass of dodecylamine and carbon nitride in an amount of 0.5 times the mass of dodecylamine, transferring the autoclave to an oven, adjusting the temperature to 180° C., keeping the temperature for 15 h, cooling to room temperature, centrifuging to obtain a carbon nitride-cadmium sulfide wet material, washing the carbon nitride-cadmium sulfide wet material with ethanol and ultrapure water alternately for 8 times, placing it in a drying oven at 60° C., and drying it for 12 h to obtain carbon nitride-cadmium sulfide;
[0035] (3) β-mercaptocyclodextrin was dispersed in ultrapure water with a mass of 2 times that of β-mercaptocyclodextrin, ultrasonically dispersed at 30kHz for 2 minutes, methanol with a mass of 0.05 times that of β-mercaptocyclodextrin and chloroform with a mass of 0.05 times that of β-mercaptocyclodextrin were added, and finally the pH was adjusted to 11 with tetramethylammonium hydroxide to obtain a mercaptocyclodextrin solution; carbon nitride-cadmium sulfide was dispersed in a mercaptocyclodextrin solution with a mass of 10 times that of carbon nitride-cadmium sulfide, stirred at room temperature and 1500rpm for 48 hours in a dark environment, acetone with a mass of 8 times that of carbon nitride-cadmium sulfide was added, and centrifuged at 7000rpm for 5 minutes to obtain a carbon nitride material, and the carbon nitride material was washed with acetone 5 times and dried in a drying oven at 80℃ for 5 hours to obtain a carbon nitride composite material for photocatalytic degradation.
[0036] Comparative Example 1
[0037] A carbon nitride composite material for photocatalytic degradation, mainly comprising, by weight:
[0038] 5 parts of carbon nitride-cadmium sulfide, 50 parts of mercaptocyclodextrin solution
[0039] A preparation method for photocatalytic degradation of carbon nitride-based composite materials, the preparation method for photocatalytic degradation of carbon nitride-based composite materials is:
[0040] (1) Melamine and sodium bicarbonate are mixed in a mass ratio of 4:1 and fully ground. After grinding, the mixture is passed through a 200-mesh sieve to obtain a melamine mixture. The mixture is transferred to a muffle furnace, heated to 520°C at 2°C / min, kept warm for 3 hours, cooled naturally to room temperature, ground again, and dispersed in 2% dilute nitric acid with a mass fraction of 10 times the mass of the melamine mixture. The mixture is stirred at room temperature and 800 rpm for 6 hours, filtered to obtain a solid, washed with ultrapure water until the washing liquid is neutral, and finally dried in a 120°C ancient wind drying oven for 12 hours to obtain carbon nitride;
[0041] (2) placing dodecylamine in a polytetrafluoroethylene-lined autoclave, heating in a water bath at 50° C. and stirring at 800 rpm for 10 min, adding cadmium acetate in an amount of 0.15 times the mass of dodecylamine, continuing to stir until completely dissolved, continuing to add thioacetamide in an amount of 0.18 times the mass of dodecylamine and carbon nitride in an amount of 0.4 times the mass of dodecylamine, transferring the autoclave to an oven, adjusting the temperature to 150° C., keeping the temperature for 12 h, cooling to room temperature, centrifuging to obtain a carbon nitride-cadmium sulfide wet material, washing the carbon nitride-cadmium sulfide wet material with ethanol and ultrapure water alternately for 6 times, placing it in a drying oven at 60° C., and drying it for 12 h to obtain carbon nitride-cadmium sulfide;
[0042] (3) β-mercaptocyclodextrin was dispersed in ultrapure water with a mass of 2 times that of β-mercaptocyclodextrin, ultrasonically dispersed at 20 kHz for 1 min, methanol with a mass of 0.03 times that of β-mercaptocyclodextrin and chloroform with a mass of 0.03 times that of β-mercaptocyclodextrin were added, and finally the pH was adjusted to 11 with tetramethylammonium hydroxide to obtain a thiolcyclodextrin solution; carbon nitride-cadmium sulfide was dispersed in a thiolcyclodextrin solution with a mass of 10 times that of carbon nitride-cadmium sulfide, stirred at room temperature and 1200 rpm in a dark environment for 48 h, acetone with a mass of 5 times that of carbon nitride-cadmium sulfide was added, and centrifuged at 7000 rpm for 3 min to obtain a carbon nitride material, and the carbon nitride material was washed with acetone 3 times and dried in a drying oven at 60°C for 3 h to obtain a carbon nitride-based composite material for photocatalytic degradation.
[0043] Comparative Example 2
[0044] A carbon nitride composite material for photocatalytic degradation, mainly comprising, by weight:
[0045] 5 parts of carbon nitride-cadmium sulfide, 50 parts of mercaptocyclodextrin solution
[0046] A preparation method for photocatalytic degradation of carbon nitride-based composite materials, the preparation method for photocatalytic degradation of carbon nitride-based composite materials is:
[0047] (1) Melamine and sodium urea are mixed in a mass ratio of 2:1 and fully ground. After grinding, the mixture is sieved with a 200-mesh screen to obtain a melamine mixture. The mixture is transferred to a muffle furnace, heated to 520°C at a rate of 2°C / min, kept warm for 3 hours, cooled naturally to room temperature, ground again, and dispersed in 2% dilute nitric acid with a mass fraction of 10 times the mass of the melamine mixture. The mixture is stirred at room temperature and 800 rpm for 6 hours, filtered to obtain a solid, washed with ultrapure water until the washing liquid is neutral, and finally dried in a 120°C ancient wind drying oven for 12 hours to obtain carbon nitride;
[0048] (2) placing dodecylamine in a polytetrafluoroethylene-lined autoclave, heating in a water bath at 50° C. and stirring at 800 rpm for 10 min, adding cadmium acetate in an amount of 0.15 times the mass of dodecylamine, continuing to stir until completely dissolved, continuing to add thioacetamide in an amount of 0.18 times the mass of dodecylamine and carbon nitride in an amount of 0.4 times the mass of dodecylamine, transferring the autoclave to an oven, adjusting the temperature to 150° C., keeping the temperature for 12 h, cooling to room temperature, centrifuging to obtain a carbon nitride-cadmium sulfide wet material, washing the carbon nitride-cadmium sulfide wet material with ethanol and ultrapure water alternately for 6 times, placing it in a drying oven at 60° C., and drying it for 12 h to obtain carbon nitride-cadmium sulfide;
[0049] (3) β-mercaptocyclodextrin was dispersed in ultrapure water with a mass of 2 times that of β-mercaptocyclodextrin, ultrasonically dispersed at 20 kHz for 1 min, methanol with a mass of 0.03 times that of β-mercaptocyclodextrin and chloroform with a mass of 0.03 times that of β-mercaptocyclodextrin were added, and finally the pH was adjusted to 11 with tetramethylammonium hydroxide to obtain a thiolcyclodextrin solution; carbon nitride-cadmium sulfide was dispersed in a thiolcyclodextrin solution with a mass of 10 times that of carbon nitride-cadmium sulfide, stirred at room temperature and 1200 rpm in a dark environment for 48 h, acetone with a mass of 5 times that of carbon nitride-cadmium sulfide was added, and centrifuged at 7000 rpm for 3 min to obtain a carbon nitride material, and the carbon nitride material was washed with acetone 3 times and dried in a drying oven at 60°C for 3 h to obtain a carbon nitride-based composite material for photocatalytic degradation.
[0050] Comparative Example 3
[0051] A carbon nitride composite material for photocatalytic degradation, mainly comprising, by weight:
[0052] 5 parts of carbon nitride-cadmium sulfide, 50 parts of mercaptocyclodextrin solution
[0053] A preparation method for photocatalytic degradation of carbon nitride-based composite materials, the preparation method for photocatalytic degradation of carbon nitride-based composite materials is:
[0054] (1) urea and sodium bicarbonate are mixed in a mass ratio of 2:1 and fully ground. After grinding, the mixture is sieved through a 200-mesh sieve to obtain a melamine mixture. The mixture is transferred to a muffle furnace, heated to 520°C at a rate of 2°C / min, kept warm for 3 hours, cooled naturally to room temperature, ground again, and dispersed in 2% dilute nitric acid with a mass fraction of 10 times the mass of the melamine mixture. The mixture is stirred at room temperature and 800 rpm for 6 hours, filtered to obtain a solid, washed with ultrapure water until the washing liquid is neutral, and finally dried in a 120°C ancient wind drying oven for 12 hours to obtain carbon nitride;
[0055] (2) placing dodecylamine in a polytetrafluoroethylene-lined autoclave, heating in a water bath at 50° C. and stirring at 800 rpm for 10 min, adding cadmium acetate in an amount of 0.15 times the mass of dodecylamine, continuing to stir until completely dissolved, continuing to add thioacetamide in an amount of 0.18 times the mass of dodecylamine and carbon nitride in an amount of 0.4 times the mass of dodecylamine, transferring the autoclave to an oven, adjusting the temperature to 150° C., keeping the temperature for 12 h, cooling to room temperature, centrifuging to obtain a carbon nitride-cadmium sulfide wet material, washing the carbon nitride-cadmium sulfide wet material with ethanol and ultrapure water alternately for 6 times, placing it in a drying oven at 60° C., and drying it for 12 h to obtain carbon nitride-cadmium sulfide;
[0056] (3) β-mercaptocyclodextrin was dispersed in ultrapure water with a mass of 2 times that of β-mercaptocyclodextrin, ultrasonically dispersed at 20 kHz for 1 min, methanol with a mass of 0.03 times that of β-mercaptocyclodextrin and chloroform with a mass of 0.03 times that of β-mercaptocyclodextrin were added, and finally the pH was adjusted to 11 with tetramethylammonium hydroxide to obtain a thiolcyclodextrin solution; carbon nitride-cadmium sulfide was dispersed in a thiolcyclodextrin solution with a mass of 10 times that of carbon nitride-cadmium sulfide, stirred at room temperature and 1200 rpm in a dark environment for 48 h, acetone with a mass of 5 times that of carbon nitride-cadmium sulfide was added, and centrifuged at 7000 rpm for 3 min to obtain a carbon nitride material, and the carbon nitride material was washed with acetone 3 times and dried in a drying oven at 60°C for 3 h to obtain a carbon nitride-based composite material for photocatalytic degradation.
[0057] Comparative Example 4
[0058] A carbon nitride composite material for photocatalytic degradation, mainly comprising, by weight:
[0059] 5 parts of carbon nitride-cadmium sulfide, 50 parts of mercaptocyclodextrin solution
[0060] A preparation method for photocatalytic degradation of carbon nitride-based composite materials, the preparation method for photocatalytic degradation of carbon nitride-based composite materials is:
[0061] (1) Melamine, urea and sodium bicarbonate are mixed in a mass ratio of 4:2:1 and fully ground. After grinding, the mixture is passed through a 200-mesh sieve to obtain a melamine mixture. The mixture is transferred to a muffle furnace, heated to 520°C at 2°C / min, kept warm for 3 hours, cooled naturally to room temperature, ground again, and dispersed in 2% dilute nitric acid with a mass fraction of 10 times the mass of the melamine mixture. The mixture is stirred at room temperature and 800 rpm for 6 hours, filtered to obtain a solid, washed with ultrapure water until the washing liquid is neutral, and finally dried in a 120°C ancient wind drying oven for 12 hours to obtain carbon nitride;
[0062] (2) Dodecylamine was placed in a polytetrafluoroethylene-lined autoclave, heated in a water bath at 50°C and stirred at 800 rpm for 10 min, cadmium acetate was added in an amount of 0.15 times the mass of dodecylamine, and stirring was continued until it was completely dissolved, and thioacetamide was added in an amount of 0.18 times the mass of dodecylamine and carbon nitride was added in an amount of 0.4 times the mass of dodecylamine, and the autoclave was transferred to an oven, the temperature was adjusted to 150°C, and the temperature was kept for 12 h. After cooling to room temperature, the carbon nitride-cadmium sulfide wet material was obtained by centrifugation, and the carbon nitride-cadmium sulfide wet material was washed alternately with ethanol and ultrapure water for 6 times, and placed in a drying oven at 60°C and dried for 12 h to obtain a carbon nitride-based composite material for photocatalytic degradation.
[0063] Effect example
[0064] Table 1 below shows the performance analysis of the carbon nitride-based composite materials for photocatalytic degradation prepared by using the preparation method of the carbon nitride-based composite materials for photocatalytic degradation in Examples 1 and 2 of the present invention and Comparative Examples 1, 2, 3, and 4.
[0065] Table 1
[0066] Degradation rate (%) Secondary degradation rate (%) Example 1 99.8 99.6 Example 2 99.8 99.7 Comparative Example 1 95.4 94.3 Comparative Example 2 94.7 92.7 Comparative Example 3 93.4 91.9 Comparative Example 4 99.3 90.4
[0067] By comparing the experimental data of Examples 1, 2, and 3 with the comparative example, it can be clearly found that the carbon nitride-based composite material for photocatalytic degradation used in the present invention and the carbon nitride-based composite material for photocatalytic degradation prepared by the preparation method thereof have high degradation rate and good stability;
[0068] From the comparison between Example 1 and Example 2, Comparative Example 1, Comparative Example 2, and Comparative Example 3, it can be found that when preparing carbon nitride, melamine, urea, and sodium bicarbonate are used to prepare carbon nitride, and the degradation rate of the prepared carbon nitride composite material is high, indicating that the prepared carbon nitride has internal structural defects, and at the same time, urea is combined to form pores, forming a passage in the carbon nitride, thereby enhancing the photocatalytic reduction ability;
[0069] From the comparison of Example 1 and Example 2 with Comparative Example 4, it can be found that after cadmium sulfide is modified on the carbon nitride with a two-dimensional planar layered stacking structure, mercaptocyclodextrin is modified on the cadmium sulfide, and cyclodextrin is used as a surface ligand to enhance the solubility and stability of cadmium sulfide in water, reduce the agglomeration of cadmium sulfide, reduce the agglomeration of carbon nitride composite materials, and improve the stability of carbon nitride composite materials.
[0070] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A carbon nitride-based composite material for photocatalytic degradation and a preparation method thereof, characterized in that: The preparation methods are: preparation of carbon nitride; preparation of carbon nitride-cadmium sulfide; preparation of carbon nitride composite materials for photocatalytic degradation.
2. The carbon nitride-based composite material for photocatalytic degradation and its preparation method according to claim 1, characterized in that: The specific steps include: (1) Melamine, urea and sodium bicarbonate are mixed and fully ground, and then passed through a 200-mesh sieve to obtain a melamine mixture. The mixture is transferred to a muffle furnace, heated to 520° C. at a rate of 2 to 4° C. / min, kept warm for 3 to 4 hours, cooled naturally to room temperature, ground again, and dispersed in 2% dilute nitric acid having a mass fraction of 10 times that of the melamine mixture, stirred at room temperature and 800 to 1200 rpm for 6 to 8 hours, filtered to obtain a solid, washed with ultrapure water until the washing liquid is neutral, and finally dried in a 120° C. oven for 12 hours to obtain carbon nitride; (2) placing dodecylamine in a polytetrafluoroethylene-lined autoclave, heating in a water bath at 50° C. and stirring at 800-1200 rpm for 10-20 min, adding cadmium acetate in an amount of 0.15-0.2 times the mass of dodecylamine, continuing to stir until completely dissolved, continuing to add thioacetamide in an amount of 0.18-0.22 times the mass of dodecylamine and carbon nitride in an amount of 0.4-0.5 times the mass of dodecylamine, transferring the autoclave to an oven, adjusting the temperature to 150-180° C., keeping the temperature for 12-15 h, cooling to room temperature, centrifuging to obtain a carbon nitride-cadmium sulfide wet material, washing the carbon nitride-cadmium sulfide wet material, placing the carbon nitride-cadmium sulfide wet material in a drying oven at 60-80° C., and drying for 12 h to obtain carbon nitride-cadmium sulfide; (3) Dispersing carbon nitride-cadmium sulfide in a thiol cyclodextrin solution with a mass of 10 to 15 times that of carbon nitride-cadmium sulfide, stirring in the dark at room temperature and 1200 to 1500 rpm for 48 hours, adding acetone with a mass of 5 to 8 times that of carbon nitride-cadmium sulfide, centrifuging at 7000 rpm for 3 to 5 minutes to obtain a carbon nitride material, washing the carbon nitride material with acetone for 3 to 5 times, and drying it in a drying oven at 60 to 80°C for 3 to 5 hours to obtain a carbon nitride-based composite material for photocatalytic degradation.
3. The carbon nitride-based composite material for photocatalytic degradation and its preparation method according to claim 2, characterized in that: In the above step (1), the mass ratio of melamine, urea and sodium bicarbonate is 4:2:1 to 5:2.5:
1.
4. The carbon nitride-based composite material for photocatalytic degradation and its preparation method according to claim 3, characterized in that: In the above step (2): during washing, the carbon nitride-cadmium sulfide wet material is washed alternately with ethanol and ultrapure water for 6 to 8 times.
5. The carbon nitride-based composite material for photocatalytic degradation and its preparation method according to claim 4, characterized in that: In the above step (3), the method for preparing the mercaptocyclodextrin solution is as follows: dispersing β-mercaptocyclodextrin in ultrapure water with a mass of 2 to 3 times that of β-mercaptocyclodextrin, ultrasonically dispersing at 20 to 30 kHz for 1 to 2 minutes, adding methanol with a mass of 0.03 to 0.05 times that of β-mercaptocyclodextrin and chloroform with a mass of 0.03 to 0.05 times that of β-mercaptocyclodextrin, and finally adjusting the pH to 11 with tetramethylammonium hydroxide to obtain a mercaptocyclodextrin solution.
6. The carbon nitride-based composite material for photocatalytic degradation and the preparation method thereof according to claim 5, characterized in that: The carbon nitride-based composite material for photocatalytic degradation and the preparation method thereof include the following raw materials in weight fractions: 5 to 10 parts of carbon nitride-cadmium sulfide and 50 to 150 parts of mercaptocyclodextrin solution; the carbon nitride-cadmium sulfide is prepared by first preparing carbon nitride with melamine, urea and sodium bicarbonate, and then generating cadmium sulfide on the carbon nitride.
Citation Information
Patent Citations
g-C3N4 nanosheet / CdS composite visible-light-driven photocatalyst
CN103785434A
Carbine-nitrene / silver carbonate composite nano-material, and preparation method and application thereof
CN107970965A
Preparation method of graphene-phase carbon nitride-cadmium sulfide composite material
CN108144635A
Carbonate modified carbon nitride, preparation method thereof and application thereof in low-concentration ammonia-nitrogen wastewater treatment
CN111715175A
Preparation and application of CdS / g-C3N4 nanotube catalyst with photocatalytic performance
CN117772256A
